2013
DOI: 10.1016/j.jacc.2013.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril and Carvedilol for Preventing Chemotherapy-Induced Left Ventricular Systolic Dysfunction in Patients With Malignant Hemopathies

Abstract: Combined treatment with enalapril and carvedilol may prevent LVSD in patients with malignant hemopathies treated with intensive chemotherapy. The clinical relevance of this strategy should be confirmed in larger studies. (Prevention of Left Ventricular Dysfunction During Chemotherapy [OVERCOME]; NCT01110824).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
207
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 550 publications
(228 citation statements)
references
References 22 publications
4
207
0
17
Order By: Relevance
“…Patients in the intervention group had a lower incidence of the combined event of death or HF (6.7% versus 22%) and of death, HF, or a final LVEF<45% (6.7% versus 24.4%). 75 A recent study also found protective effects on LVEF decline with the use of a combination of candesartan and carvedilol. 76 Finally, a study has recently reported the preventive effects of spironolactone on anthracycline-induced myocardial toxicity in patients with breast cancer.…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients in the intervention group had a lower incidence of the combined event of death or HF (6.7% versus 22%) and of death, HF, or a final LVEF<45% (6.7% versus 24.4%). 75 A recent study also found protective effects on LVEF decline with the use of a combination of candesartan and carvedilol. 76 Finally, a study has recently reported the preventive effects of spironolactone on anthracycline-induced myocardial toxicity in patients with breast cancer.…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 93%
“…In a recent study, the administration of enalapril and carvedilol in patients with hematological malignancies 75 prevented LVEF decline at 6 months, especially in patients with acute leukemia, a group of patients who received more intensive chemotherapy with repeated doses of anthracyclines. Patients in the intervention group had a lower incidence of the combined event of death or HF (6.7% versus 22%) and of death, HF, or a final LVEF<45% (6.7% versus 24.4%).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
“…Observational studies and small randomized clinical trials suggest a benefit in early initiation of angiotensin‐converting enzyme inhibitors and beta‐blockers for the prevention of cardiotoxicity 15, 89, 90, 91, 92, 93. The PRADA (Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy) trial tested whether angiotensin receptor blockers and/or beta‐blockers would be effective in preventing cardiotoxicity in patients diagnosed with breast cancer receiving anthracycline‐based chemotherapy with and without trastuzumab.…”
Section: Prevention and Treatment Of Cardiotoxicity Associated With Hmentioning
confidence: 99%
“…Не было получено статистически значимых различий в таких показателях, как общая смертность (Р=0,11), количество больных со сниже-нием ФИ >10% (Р=0,90), ХСН или снижение ФИ >10% (Р=0,22), количество тяжелых нежелательных явлений (Р=0,15). Авторы приходят к выводу, что профилактическое назначение эналаприла вместе с карведилолом перед и во время полихимиотерапии предотвращает левожелудочковую дисфункцию [26].…”
Section: таблица 1 продолжениеunclassified